The investigation of Consequences of Conquests in the First Islamic Decades - khalil zarei; shokouhosadat arabi hashemi; Siavash Yari (تاریخ اسلام)
The conquests of Muslims faced the world of Islam with problems, so that some specific strategies were taken by the early caliphs to settle them. The inclination of plunders toward the center of caliphate, the possession of habitants’ farming lands in the newly conquered lands, the foundation of casern in city as well as the migration of Arab Muslims to Iran were considered the outcomes of conquests. In spite of some benefits for the Muslims, they were along with some detriments for the new Islamic society on one hand and the newly conquered areas of Iran on the other hand. The detriments such as putting outstanding followers aside, unfair division of plunders, development of Nobel class, heterogeneous composition of population in the caserns of cities, reoccurrence of racial prejudices, no fundamental propagation of Islam, no supervision on the conduct of agents related to the reception of tax and development of a great branch of proprietors in Hejaz.The present research investigates and criticizes the consequences of conquests through the descriptive-analytical method of research